Dietary supplementation with Tolypocladium sinense mycelium prevents dyslipidemia inflammation in high fat diet mice by modulation of gut microbiota in mice - Wang, Xiaolong; Li, Lin; Bai, Mingjian; Zhao, Jiaxin; Sun, Xiaojie; Gao, Yu; Yu, Haitao; Chen, Xia; Zhang, Chunjing (Frontiers in Immunology, 2022)
Obesity is a risk factor for many serious health problems, associated with inflammation, hyperlipidemia, and gut dysbiosis. Prevention of obesity is especially important for human health. Tolypocladium sinense is one of the fungi isolated from Chinese caterpillar fungus, which is a traditional Chinese medicine with putative gut microbiota modulation effects. Here, we established a high-fat diet (HFD)-induced hyperlipidemia mice model, which was supplemented with lyophilized T. sinense mycelium (TSP) daily to evaluate its anti-obesity effects. The results indicated that TSP supplementation can effectively alleviate the inflammatory response and oxidative stress levels caused by obesity. TSP significantly prevented obesity and suppressed dyslipidemia by regulating the expression of lipid metabolism genes in the liver. TSP is also effective in preventing the HFD-induced decline in short-chain fatty acid (SCFA) content. Gut microbiota profiling showed that TSP supplementation reversed HFD diet-induced bacterial abundance and also altered the metabolic pathways of functional microorganisms, as revealed by KEGG analysis. It is noteworthy that, structural equation model (SEM) constructed based on our research results showed a regulatory role of the enteric-liver axis, whereby up-regulated gut microbiota (Lactobacillus and Prevotella_9) can act directly on gene expression of liver lipid metabolism and indirectly regulate lipid metabolism parameters and LPS, ultimately reducing the inflammatory response. Additionally, the role of TSP in the regulation of lipid metabolism was reconfirmed by fecal microbiota transplantation. To sum up, our results provide the evidence that TSP may be used as prebiotic agents to prevent obesity by altering the gut microbiota, alleviating the inflammatory response and regulating gene expression of liver lipid metabolism.